IN-VIVO EVALUATION OF ANTI-COCCIDIAL EFFICACY OF SALINOMYCIN AND AMPROLIUM IN COMMERCIAL CHICKEN - R. Selvarani; M. Raman; S. Gomathinayagam (Indian Journal of Veterinary and Animal Sciences Research, 2024)
In - vivo evaluation of the efficacy of test anti - coccidial efficacy of salinomycin and amprolium carried out in two different trials in 228 commercial chicken revealed 100% efficacy against mixed eimeria sp on comparative evaluation with standed in feed anti - coccidials. There was marked reduction in the oocyst output with increased body weight gain and improved feed conversation efficiency in the experimental study.